2015
DOI: 10.17499/jsser.88468
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Citizenship and Democracy Education Textbook and Curriculum in terms of Global Education

Abstract: As a result of scientific and technological developments in today's world, global education has started to take its place in the educational systems throughout the world and become more significant in recent years.Since global education has multiple effects on societies, it is also crucial in helping students to become informed, active, and global citizens. This study employs document analysis, a qualitative research method, in order to examine how the themes regarding global education are shaped in the Citize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…However, the participants emphasized that the social studies curriculum and social studies teacher education programs in Turkey lacked providing students with such skills. Likewise, Açıkalın (2010aAçıkalın ( , 2010b, Günel and Pehlivan (2015), and Günel and Pehlivan (2016) The participants also explained that they have learned about different cultures through media, social media, and their peers. They added that the only time they have learned about different cultures exist both within and outside of Turkey in-class was during the "Global Education"…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the participants emphasized that the social studies curriculum and social studies teacher education programs in Turkey lacked providing students with such skills. Likewise, Açıkalın (2010aAçıkalın ( , 2010b, Günel and Pehlivan (2015), and Günel and Pehlivan (2016) The participants also explained that they have learned about different cultures through media, social media, and their peers. They added that the only time they have learned about different cultures exist both within and outside of Turkey in-class was during the "Global Education"…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Throughout the existing literature, it has been suggested that the themes of global education are not entirely represented in the social studies curriculum in Turkey (Açıkalın, 2010a;Balkar and Özgan, 2010;Günel and Pehlivan, 2015;Kaymakçı, 2012). Researchers also pointed out that multiple perspectives as one of the themes is diminished or ignored across the curriculum and the textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…Alanyazın incelendiğinde, gerek yurtiçi gerekse yurt dışında küresel eğitimin öğrenme-öğretme sürecini ve programdaki yerini konu alan çalışmaların olduğu görülmektedir (Açıkalın, 2010;Appleyard, 2009;Balkar & Özgan, 2010;Günel & Pehlivan, 2015;Kaymakçı, 2012;Mangram & Watson, 2011;Mundy & Manion, 2008, Özkan, 2006. Öğrenme-öğretme sürecinde yapılan çalışmalarda, genellikle öğretmen ve öğrencilerin küresel eğitim ve ilişkili kavramlara ilişkin görüşleri belirlenmeye çalışılmıştır.…”
Section: Alanyazınunclassified
“…The social studies curriculum in Turkey has historically supported nationalist ideologies. Critics argued that the curriculum's emphasis on a nationalistic narrative might result in partial interpretations of historical events, failing to provide a comprehensive understanding of various perspectives (Acikalin, 2010;Ersoy, 2013;Günel & Pehlivan, 2015). This might cause the dissemination of prejudice and hatred, as well as the marginalization or erasure of specific ethnic, religious, or cultural communities.…”
Section: The School System and Social Studies As A Subject In Turkeymentioning
confidence: 99%
“…In conclusion, the social studies textbooks in Turkey demonstrate both strengths and limitations in their approach to conceptualizing and teaching global citizenship. Research indicated that social studies textbooks in Turkey (Acikalin, 2010;Arar et al, 2016;Ersoy, 2013;Günel & Pehlivan, 2015;Günel, 2016;Kilinc & Tarman, 2018) as well as in numerous other countries (Evans, 2003;Philippou, 2009;Su, 2007) do not adequately address the concept of global citizenship. The incorporation of global citizenship education into educational materials and curricula is limited without sufficient emphasis on social justice, highlighting a widespread gap in promoting a broader understanding of global issues, intercultural competence, and fostering a sense of responsibility towards the global community.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%